Implementasi Pembelajaran Mata Kuliah Kewirausahaan untuk Meningkatkan Minat Mahasiswa Berwirausaha Program Studi Pendidikan Ekonomi Universitas Mulawarman - Nursahira; Abdul Rachim; Riyo Riyadi (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
The aim of this research is to determine the implementation of learning in entrepreneurship courses to increase students' interest in entrepreneurship in the Mulawarman University Economic Education Study Program. This research is descriptive research with a qualitative approach. Data collection uses interviews. The data analysis used is data reduction, data presentation, and verification/drawing conclusions. 1). Understanding of entrepreneurship course material, where students enjoy learning entrepreneurship courses and pay enough attention when the lecturer explains the material, 2). Entrepreneurship training, where students are interested in taking part in entrepreneurship training held on campus or outside campus, 3). Dare to take risks, where students have the courage to take risks without feeling afraid of the risks that will occur, 4). Observing activities about entrepreneurship, where students only need to pay attention to tips or tricks from someone who has been successful in entrepreneurship, 5). Participate in entrepreneurial activities, where students take part in seminar activities and have been involved in the business activities of family and friends.